1993
DOI: 10.1016/s0886-3350(13)80276-3
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaccommodation with the 3M diffractive multifocal intraocular lens: A refraction study of 52 subjects

Abstract: A refraction study was performed of 52 pseudophakic subjects implanted with a 3M diffractive intraocular lens (IOL). Twenty patients implanted with conventional monofocal IOLs from 3M were used as controls. The refraction for distance and near was determined, corresponding to the refractive (distance vision) and diffractive (near vision) foci. Pseudoaccommodation amplitude was measured relative to the variation of visual acuity as a function of "fogging" obtained with plus and minus lenses over any required sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…This is an important method to assess and compare the satisfaction of subjects included in the four groups (17,18) . It is also in agreement with the idea that hyperopic patients would have milder symptoms than myopic patients, although this comparison was not done in this study (19) .There was no difference in spherical equivalent between study groups. The refractive outcome was very close to emmetropia, which was our goal.…”
supporting
confidence: 90%
“…This is an important method to assess and compare the satisfaction of subjects included in the four groups (17,18) . It is also in agreement with the idea that hyperopic patients would have milder symptoms than myopic patients, although this comparison was not done in this study (19) .There was no difference in spherical equivalent between study groups. The refractive outcome was very close to emmetropia, which was our goal.…”
supporting
confidence: 90%
“…Steinert et al [1] reported that the focal depth of eyes with the AMO Array multifocal IOL was 1.00 dpt wider than that of eyes with monofocal IOLs 1 year postoperatively. Bellucci and Giardini [2] compared the 3M diffractive multifocal IOLs with monofocal IOLs and concluded that the average accommodative ability of multifocal IOL was 2- to 3-fold greater than that of monofocal IOLs. Weghaupt et al [3] suggested that 3.00–4.00 dpt focal depth were ideal without decreasing the whole range.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of refractive and diffractive multifocal IOLs provides only a partial solution as these IOLs are associated with a high incidence of side effects such as halos, flare, glare, and reduced visual acuity and contrast sensitivity. [15][16][17] Thus, accommodating IOLs that can focus on objects at different distances by an anterior shift of the optic caused by ciliary muscle contraction have been recently proposed. [18][19][20][21] There is considerable current research of the measurement of accommodative changes in refracting power and of objective methods that can demonstrate biometric changes in the eye.…”
mentioning
confidence: 99%